Pengaruh Biaya Produksi Dan Biaya Operasional Terhadap Peningkatan Laba PT Mayora Indah Tbk Tahun 2013-2024 - Rizca Monica Prameswari; Hasudungan Pangaribuan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. The purpose of this study is to examine the effect of production costs and operating costs partially and simultaneously on the net profit of PT Mayora Indah Tbk. This research employs a quantitative method using secondary data in the form of the company’s annual financial statements for the period 2013–2024. Data analysis was conducted using multiple linear regression analysis, t-test, F-test, and coefficient of determination, after first performing classical assumption tests. The results of the study indicate that partially, production costs do not have a significant effect on net profit. This is evidenced by a significance value of 0.052 > 0.05 and a t-value of 2.238 < t-table of 2.262, indicating that the null hypothesis (H₀) is accepted and the alternative hypothesis (H₁) is rejected. Operating costs partially also do not have a significant effect on net profit, as shown by a significance value of 0.880 > 0.05 and a t-value of 0.156 < t-table of 2.262, indicating that the null hypothesis (H₀) is accepted and the alternative hypothesis (H₂) is rejected. However, simultaneously, production costs and operating costs have a significant effect on the net profit of PT Mayora Indah Tbk, as indicated by an F-value of 6.964 > F-table of 4.26 with a significance level of 0.015 < 0.05. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₃) is accepted. Thus, it can be concluded that although each variable does not have a significant effect partially, production costs and operating costs simultaneously provide a significant contribution to changes in the company’s net profit.